GAMBARAN TINGKAT KESEHATAN GIGI ANAK USIA DINI BERDASARKAN INDEKS def-t PADA SISWA PAUD KELURAHAN JATI KOTA PADANG - Aida Fitriana; Nila Kasuma (Andalas Dental Journal, 2013)
Dental caries is the most common problem in the world. Tooth and oral diseases are most common lessions in Indonesian society (60%). The purpose of this study was to find out the index of def-t PAUD students of Kelurahan Jati Padang city which is can be use to guide planning, actuating, controlling and evaluating dental health programme by Dentistry Faculty of Andalas University. The research has been used descriptive methode and used total sampling. Samples consist for def-t index was 13 girls and 20 boys and categorized based on WHO caries categorize. The result has been shown that def-t index PAUD studentsi is 5,18. The summarized from this research have been shown that def-t PAUD students in highly categorized.